EFSUMB Guidelines on Interventional Ultrasound (INVUS), Part I - General Aspects (long Version) - Lorentzen, T.; Nolsoe, C. P.; Ewertsen, C.; Nielsen, M. B.; Leen, E.; Havre, R. F.; Gritzmann, N.; Brkljacic, Boris; Nuernberg, D.; Kabaalioglu, A.; Strobel, Deike; Jenssen, C.; et al. (Ultraschall in der Medizin, 2015)
This is the first part of the Guidelines on Interventional Ultrasound of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) and covers all general aspects of ultrasound-guided procedures (long version).
EVALuna2:2038